2019
DOI: 10.1590/0074-02760190149
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Echinococcus vogeli in the western Brazilian Amazon

Abstract: Human polycystic echinococcosis is a parasitic infection caused by the larval stage of Echinococcus vogeli, which occurs in rural areas of Central and South America. Until now, little information on the genetic variability of E. vogeli is available. Here, 32 samples from human-excised E. vogeli cysts had a 396-bp sequence of the mitochondrial cytochrome oxidase I (COI) gene sequenced and compared to another 17 COI sequences representing nine Echinococcus species. A Bayesian COI tree revealed that all E. vogeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…This monophyletic result was more recently confirmed for E. vogeli after studies on its genetic diversity carried out in Western Brazilian Amazon [44,45]. In addition, mitochondrial and nuclear sequence polymorphisms carried out with 38 isolates of E. vogeli from humans and wild animal hosts from Amazonian Regions revealed that E. vogeli is partially synanthropic, with a diverse population near or in association ecologically with humans [44,45]. The use of molecular tools has shown differences in nucleic acid sequences that reflect phenotypic variation, and the phenotypic and genetic characteristics complement the previous observations published by the descriptive parasitologists years ago [20].…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…This monophyletic result was more recently confirmed for E. vogeli after studies on its genetic diversity carried out in Western Brazilian Amazon [44,45]. In addition, mitochondrial and nuclear sequence polymorphisms carried out with 38 isolates of E. vogeli from humans and wild animal hosts from Amazonian Regions revealed that E. vogeli is partially synanthropic, with a diverse population near or in association ecologically with humans [44,45]. The use of molecular tools has shown differences in nucleic acid sequences that reflect phenotypic variation, and the phenotypic and genetic characteristics complement the previous observations published by the descriptive parasitologists years ago [20].…”
Section: Resultsmentioning
confidence: 55%
“…These studies concluded that the origin of the two species of Neotropical Echinococcus appears to be monophyletic; in other words, both share a common ancestor [42,43]. This monophyletic result was more recently confirmed for E. vogeli after studies on its genetic diversity carried out in Western Brazilian Amazon [44,45]. In addition, mitochondrial and nuclear sequence polymorphisms carried out with 38 isolates of E. vogeli from humans and wild animal hosts from Amazonian Regions revealed that E. vogeli is partially synanthropic, with a diverse population near or in association ecologically with humans [44,45].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…There are no other published records of the infection of agouti by E. vogeli in the Amazon region. Most human cases of neotropical echinococcosis recorded in Brazil come from the Amazon region, where the disease is commonly known as "Paca Disease" (D'Alessandro & Rausch 2008, Daipert-Garcia et al 2019). In the state of Amazonas, six cases of the disease were reported (Guimarães et al 2005;Siqueira et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the state of Amazonas, six cases of the disease were reported (Guimarães et al 2005;Siqueira et al 2013). In the state of Acre, many human cases have been recorded since 1992 (Meneghelli et al 1992, Daipert-Garcia et al 2019, which reflects the continuity of the parasitic cycle of the disease in the Amazon region. Three studies estimated the prevalence of infection in Acre based on serum antibody levels.…”
Section: Discussionmentioning
confidence: 99%